2002
DOI: 10.1007/s00414-002-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Forensic approach of fatal dog attacks: a case report and literature review

Abstract: Over 1 million dog bites occur every year in the USA, however, fatal dog bites are rare and mostly affect children under 4 years of age and old people. Usually pet dogs are involved and only recently has public awareness of this health problem increased. As an example of a forensic approach we present the case of a 6-year-old girl who was killed by the three pet Rottweilers of her father. The present report includes the investigation of the death scene, the autopsy findings and the results of the examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 25 publications
0
64
0
4
Order By: Relevance
“…The pattern of injuries typically seen in fatal dog attacks is a result of both dog-and victim-related characteristics. Dogs have 42 teeth (20 upper and 22 lower), and can generate vertical force greater than 450 psi (11,12). Because of the configuration of the canine jaw, a combination of puncture wounds from the canine teeth and lacerations and/or abrasions from the incisors may be seen.…”
Section: Case #mentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of injuries typically seen in fatal dog attacks is a result of both dog-and victim-related characteristics. Dogs have 42 teeth (20 upper and 22 lower), and can generate vertical force greater than 450 psi (11,12). Because of the configuration of the canine jaw, a combination of puncture wounds from the canine teeth and lacerations and/or abrasions from the incisors may be seen.…”
Section: Case #mentioning
confidence: 99%
“…Additional injuries, including blunt force injuries, may occur because of the severe shaking, crushing, and twisting that occur after the initial bite. Most fatal injuries involve the head and neck, including asphyxia because of compression of the larynx and exsanguination because of injury of major blood vessels (11,13,14). If the victim is upright, initial bites may be directed to the back of the legs (15).…”
Section: Case #mentioning
confidence: 99%
“…Consequently, a differentiation of various bites caused by dogs of the same breed is normally not possible. However, the analysis can help to identify the offender dog (De Munnynck & Van de Voorde, 2002), moreover in bite marks analysis registered on inanimate objects, found in crime scene (bones, wood, wax as in this study, etc. ).…”
Section: Discussionmentioning
confidence: 92%
“…are seen [7,9,10,12,25] (Figures 7 and 8). Canidae uses its mandibular and maxillary canine teeth during feeding and create punctures and multiple numbers of adjacent tears in the soft tissue caused by shear-bites, which are termed as "one hole-one tear" combination [81]. The animal uses this region as a fulcrum, counteracts the weight of the corpse, and rapidly shakes its head repetitively from right to left and vice versa to pluck the tissue and creates stretch-rupture defects [25].…”
Section: Attacks Of Land Animals During Postmortem Periodmentioning
confidence: 99%
“…When teeth marks of an animal were detected on a corpse in indoor settings, if on the incident site Pitbulls, Rottweiler, and German shepherd dogs are found, then the possibility of an antemortem attack should also be considered. Indeed, these dog breeds are "convicts" [49,81,87,88]. It has been thought that pet dogs have regular food sources and do not feed on corpses; however, when they take a walk outside, they can also feed on corpses, and it has been indicated that in some circumstances, they may be unknown but important members of fauna consume corpses in the open air [5].…”
Section: Attacks Of Land Animals During Postmortem Periodmentioning
confidence: 99%